La motricidad - Preciado Loayza, Petronila (2021)
The professional sufficiency work entitled motor skills theoretically and pedagogically supports a learning experience corresponding to the psychomotor area, aimed at 4-year-old children from the town of Villa San Isidro Corrales - Tumbes, considering an important issue in the development of the child / a, since this area tends to develop in the child all his possibilities of appropriation of knowledge to modify himself and become a being capable of developing by himself which implies in the child doing, think, feel, know, communicate and want, finding themselves in a constant process of the construction of their being; through the dynamic process of motor skills. In the introductory part, the characteristics of the place where the activity took place are described, the purposes that led to the choice of the work topic, the justification and importance of the work in the optimal development of motor skills in children. The theoretical support presented conceptual foundations of the area of motor skills and the importance it has in developing not only physical abilities in the children of the town of Villa San Isidro Corrales, but also their identity, self-esteem, and the progressive discovery of their own body as a source of sensations, the exploration of the possibilities of action and bodily functions. In other words, from this approach, they seek to contribute to their training and comprehensive development process for their own well-being and that of their environment. In the pedagogical support, the didactic strategy applied to generate meaningful learning in 4-year-old children is described, as well as the theory that supports the learning session called action learning, we mention the resources to be used in the learning process , the pedagogical processes and the didactic processes that led to achieve the integral formation of the students. To finalize the present work, I have considered the conclusions that I have been able to reach in the execution of this habilitation work.